Desarchivar para anarchivar: prácticas performáticas en el umbral de lo íntimo. Reflexión en torno al ciclo Mis documentos de Lola Arias - Denise Cobello (IdeAs)
In Argentina, interest for the archive and the document in contemporary scenic creation became particularly important at the beginning of the 2000s, mainly with artists such as Vivi Tellas and Lola Arias. Many of the productions of the last two decades have been characterized by an inquiry into the documentary through hybridization between theater and conceptual art. In the present work we intend to study the use of personal files in the series Mis Documentos (2012-2017) presented in Buenos Aires in five editions under the curatorship of Lola Arias. The study about the power of the archive and its intrinsic tensions will allow us to characterize how the performing arts use the problems that the very notion triggers to challenge the archival paradigms and explore the paths of the anarchive.